The Home Country’s Role in Shaping Chinese Immigrant Entrepreneurship - Zhang, Zhiheng (Auckland University of Technology, 2010)
In the recent literature on immigrants, immigration is a complex phenomenon, characterised by a blurred boundary between the country of origin and the host country; the appearance of high and low skilled immigrants and global cities. This thesis argues, firstly that the country of origin plays an increasingly important role in influencing immigrants’ economic activities. Secondly, that highly skilled immigrant entrepreneurs have their own characteristics of economic activities. Thirdly, that between the global cities and non-global cities, immigrant entrepreneurs have different opportunity structures and strategies to operate their businesses. Global cities (or world cities) are cities that are deemed to be important nodes in the international economic network. They are large metropolitan urban centres such as Tokyo and New York, important international trade and financial capitals within the global economic network. The main research questions are ‘How do changes in the country of origin influence the characteristics of high skilled Chinese immigrant entrepreneurs? How do changes in the country of origin influence the opportunity structures and business operational behaviours of high skilled Chinese immigrant entrepreneurs between a large metropolitan and a small city - each with a different co-ethnic population size?’ These were addressed by exploring a sample population of highly skilled Chinese immigrant entrepreneurs in Auckland (a large metropolitan) and Hamilton (a small city) in relation to their characteristics in modern society; their business opportunities and the strategies they used. Seventy-seven Chinese immigrants from China were interviewed. This study found that, unlike in non-world cities, Chinese immigrant entrepreneurs in world cities did not fit the Aldrich and Waldinger (1990) model (the AW Model). Environmental changes in the host and the country of origin, the technology and the immigration movements are the main reasons. Over the last decade, more than 10 million Chinese, consisting of Chinese visitors and immigrants, went abroad each year for education, business and tourism. In turn, Chinese immigrant entrepreneurs have formed an international community, or a ‘Trans-Migrant Entrepreneurs (the TMEs)’ community in advanced countries such as New Zealand, Australia, Canada and the USA. Such an international phenomenon is fundamentally different from the activities of Chinese immigrant entrepreneurs three or more decades ago. The change can be accounted for in considerable part by their country of origin – China – that plays an important role in influencing and connecting the overseas Chinese immigrant entrepreneurs worldwide, particularly in the world cities. This thesis introduces the Zhang Model that helps to understand the different characteristics, opportunity structures and strategies relating to highly skilled Chinese immigrant entrepreneurship from those of earlier generations of immigrant entrepreneurship in the AW Model. Furthermore, based on the Zhang Model, this thesis introduced the TMEs Model that puts an emphasis primarily on highly skilled immigrants who are mainly professional service providers, looking after co-ethnic international students, tourists, immigration applicants and business investors. The introduction of the Zhang Model and the TMEs Model is the theoretical contribution of this thesis. The TMEs phenomenon is new and growing and therefore necessary to study and understand. The TMEs provide channels to enable co-ethnic people to become internationalised and promote the host country in the international market. Both their country of origin and the host nation should consider offering supportive policies to their entrepreneurship. To understand how changes in the country of origin influence immigrant entrepreneurships, further research should consider a comparative study between low and highly skilled immigrant entrepreneurships, particularly in non-global cities, the non-ethnic market. In addition, more study is needed for how the one child policy impacts on Chinese immigrant entrepreneurship.
Keywords: Chinese immigrant entrepreneurs; Home country (country of origin); Global cities; Trans-Migrant Entrepreneurs (TMEs); New Zealand; Qualitative study